Healthcare Worker Attitudes to Living Donation Prior to Planned Withdrawal of Care - Smruti Rath, MD; Claire Luo, MD; Laura Washburn, MD; Matthew Brent Price, MD; Matthew Goss, MD; Priyanka Moolchandani, MD; Sandra Parsons, PhD; Abbas Rana, MD, FACS; John Goss, MD, FACS; Nhu Thao Nguyen Galván, MD, MPH, FACS (Annals of Surgery Open)
Background and Aims:. This study assesses the attitudes of healthcare practitioners toward Living Donation Prior to Planned Withdrawal of Care (LD-PPW): the recovery of a living donor organ before withdrawal of life-sustaining measures in a patient who does not meet criteria for brain death, but for whom medical care toward meaningful recovery is deemed futile. Methods:. An electronic survey was administered to 1735 members of the American Society of Transplant Surgeons mailing list with 187 responses (10.8%). Results:. Data from this study revealed that 70% of responding practitioners agreed with LD-PPW due to principles of beneficence and autonomy. Also, 65% of participants felt confident in their ability to declare the futility of care and 70% felt that LD-PPW should be added as an option when registering to become an organ donor. Conclusion:. Currently, nearly half of all donation after circulatory determination of death do not proceed to donation. LD-PPW has been proposed as an alternative procedure targeted at increasing the quality and quantity of transplantable organs while respecting the donor’s right to donate, though its implementation has been hindered by concerns over public and provider perception. This study revealed support for LD-PPW among healthcare practitioners as an alternative procedure to increase the quality and quantity of transplantable organs while respecting the donor’s right to donate.